Pengaruh Beban Kerja Dan Stres Kerja Terhadap Kinerja Pegawai Pada Dinas Lingkungan Hidup Dan Kehutanan Provinsi Sumatera Utara - Sanjaya, Mhd Sajid; Wahyuni, Neni Sri; Bakhtiar, Bakhtiar (Universitas Medan Area, 2025)
This study aims to determine the effect of workload and work stress on employee performance at the Environment and Forestry Service of North Sumatra Province. The approach used in this research is quantitative with a population of 142 people and sampling using the slovin formula with a standard error of 10% so that a sample size of 59 respondents is obtained. The data collection technique used a questionnaire distributed to respondents who were sampled. The data analysis technique in this study is multiple linear regression analysis. The results of this study indicate that: (1) workload has a positive and significant effect on performance at the North Sumatra Province Environment and Forestry Service, (2) work stress has a positive and significant effect on employee performance at the North Sumatra Province Environment and Forestry Service, (3) workload and work stress have a positive and significant effect on employee performance at the North Sumatra Province Environment and Forestry Service.